Evaluation of the enhanced resistance of Ogataea (Hansenula) polymorpha to benzalkonium chloride as a resource for bioremediation technologies. (December 2019) - Muter, Olga; Khroustalyova, Galina; Rimkus, Alina; Kalderis, Dimitrios; Ruchala, Justyna; Sibirny, Andriy; Rapoport, Alexander
Graphical abstract: Highlights: O. polymorpha cat8Δ showed a higher resistance to BAC than wt in agar diffusion test. Growth of wt, cat8Δ on xylose stimulated (p < 0.05) respiration in 100 mg/L BAC, compared to glucose. Yeast immobilized on plastic units removed more (p < 0.05) BAC than a sterile carrier. Abstract: Benzalkonium chloride (BAC) is highly abundant in wastewaters due to its wide application in household and industrial products. The aim of this research was to compare the resistance of two genetically related strains, Ogataea polymorpha (wild type) and O. polymorpha cat8 Δ (recombinant strain), to enhanced concentrations of BAC (≥ 100 mg/L) in terms of its appearance in wastewaters. Inhibition of the respiration activity of wt and cat8Δ by 100 mg/L and 300 mg/L BAC in a xylose-containing broth (4 g/L xylose) was dependent on the carbon source used for obtaining the yeast biomass through ethanol fermentation. The respiration activity of wt in a liquid broth was inhibited by BAC, while cat8Δ strain cells were characterized by similar amounts of CO2 in the control and BAC-amended sets after 20 h of incubation and varied in range from 73.4 to 82.0 μgCO2 /h for 10 8 CFU. In an agar diffusion assay, the resistance of both yeast strains to 12 μg BAC was dependent on the medium composition. BAC-removal activity was demonstrated for yeast cells immobilized on plastic units.